2017
DOI: 10.1371/journal.pone.0183442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of average travel delay caused by moving bottlenecks on highways

Abstract: This paper presents a modelling framework to evaluate travel delay of all vehicles influenced by moving bottlenecks on highways. During the derivation of analytical formulas, the arrival of slow vehicles was approximated by a Poisson process based on the assumption that they occupied a constant low proportion of the traffic stream. The mathematical analysis process was developed from moving bottlenecks with the same velocity to those with multiple different velocities, and the closed-form expression of expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although high speed is widely regarded as one of the primary causes of accidents [34], some participants pointed out that lower speeds resulting from various factors, such as tra c, speed reduction measures, infrastructure issues, and worn-out vehicles, can create moving bottlenecks or reduce average travel speed, leading to improper compensatory actions by drivers. Studies have indicated that this situation results in longer travel times, increased tra c con icts, and a higher rate of accidents [35,36]. The interaction of these conditions with loading problems and obligatory non-driving activities in cargo and public transportation may lead to driver fatigue, rushing, or frustration that may result in aggressive driving [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although high speed is widely regarded as one of the primary causes of accidents [34], some participants pointed out that lower speeds resulting from various factors, such as tra c, speed reduction measures, infrastructure issues, and worn-out vehicles, can create moving bottlenecks or reduce average travel speed, leading to improper compensatory actions by drivers. Studies have indicated that this situation results in longer travel times, increased tra c con icts, and a higher rate of accidents [35,36]. The interaction of these conditions with loading problems and obligatory non-driving activities in cargo and public transportation may lead to driver fatigue, rushing, or frustration that may result in aggressive driving [37].…”
Section: Discussionmentioning
confidence: 99%
“…The capacity could reflect multiple properties of the model, and it is the most sensitive to route choice behavior. If the capacity of the VISSIM model is similar to the collected data, then the VISSIM model accuracy could be confirmed, and the VISSIM model could be used to evaluate the improvement of the design for traffic flow [59]. The capacity can be calculated by Eq 7: where C denotes the ideal capacity (veh/h).…”
Section: Datamentioning
confidence: 99%
“…The difference between the time for free-flowing traffic and the actual time taken is called the travel time delay [6]. Traffic bottlenecks increase this delay [7]. Traffic bottlenecks can be categorized as stationary or moving [8,9].…”
Section: Introductionmentioning
confidence: 99%